Choosing the right study design in genetic epidemiology - Thomas, Duncan (Henry Stewart Talks, 2004)
Mendelian vs. complex diseases, Approaches to gene discovery, Overview of linkage and association analysis, Association study designs, Control for population stratification, Use of younger siblings as controls, Complications and subtleties, Combining analyses using different designs, Power for association studies
Archived at 2021/02/25